2000
DOI: 10.1046/j.1365-2605.2000.00199.x
|View full text |Cite
|
Sign up to set email alerts
|

Computer‐assisted assessment of sperm morphology: comparison with conventional techniques

Abstract: The aim of the present study was to compare conventional and computer-assisted morphology assessment of spermatozoa. Sixty-two semen samples from patients undergoing in vitro fertilization (IVF) and 40 samples from patients undergoing an intracytoplasmic sperm injection (ICSI) were studied using both techniques. The percentage of normal spermatozoa found was closely correlated between the techniques (r=0.788, p < 0.0001). The intra-operator variation was low for both techniques but the inter-operator variation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…Our data were similar to previous studies that reported equal clinical relevance in the conventional and computer assisted techniques of morphology assessment [Marnet et al 2000]. …”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our data were similar to previous studies that reported equal clinical relevance in the conventional and computer assisted techniques of morphology assessment [Marnet et al 2000]. …”
Section: Discussionsupporting
confidence: 92%
“…Some studies claim that different staining techniques are both effective and reliable [Menkveld et al 1997;Marnet et al 2000;Graves et al 2005]. However, other studies have shown marked differences between stains with regard to stain intensity, differentiation, and contrast, but more importantly sperm size and shape, all of which may significantly influence the outcomes of morphology evaluation [Coetzee et al 2001].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An HTM-IVOS analyzer version 12.3 (Hamilton-Thorne Biosciences, Beverly, MA, USA) was used. The spermatozoon was identified and then analyzed by computerized software according to strict criteria [17,18].…”
Section: Conventional Sperm Parameter Assessment Before An Art Attemptmentioning
confidence: 99%